1989
DOI: 10.1002/mrm.1910110210
|View full text |Cite
|
Sign up to set email alerts
|

High‐Resolution NMR imaging of an antigen‐induced arthritis in the Rabbit Knee

Abstract: High-resolution, serial, spin-echo images were obtained for an antigen-induced knee arthritis in six rabbits. The animals were imaged prior to intra-articular challenge and at various time points up to 14 weeks after challenge. Extensive high-signal inflammatory changes were seen at Day 1 in the lymph node, capsule, and surrounding muscle. The muscle and lymph node response decreased rapidly after the first week. The capsule high-signal area reached a maximum at Day 10, but was still extensive at Day 39. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

1993
1993
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 18 publications
1
12
1
Order By: Relevance
“…Our observations in rabbit immune arthritis agree with other reports on the pattern of chondrocyte-mediated cartilage degradation [6] and synovial fibrosis [2,6]. The correlation between magnetic resonance properties and proteoglycan content in human cadaveric cartilage has been studied [-7, 8].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our observations in rabbit immune arthritis agree with other reports on the pattern of chondrocyte-mediated cartilage degradation [6] and synovial fibrosis [2,6]. The correlation between magnetic resonance properties and proteoglycan content in human cadaveric cartilage has been studied [-7, 8].…”
Section: Discussionsupporting
confidence: 94%
“…We have previously reported that cartilage thickness is reduced in magnetic resonance images (MRI) of rabbit knees injected intra-articularly with papain to degrade the cartilage extracellular proteoglycan matrix [1]. MRI of antigen-induced immune arthritis in rabbits [2] revealed fluids associated with inflammaCorrespondence to: Elizabeth M. O'Byrne, Ph.D., Research Department, Pharmaceuticals Division, Ciba-Geigy Corporation, Summit NJ 07901, USA tion and proliferative synovitis. MRI of mature rabbit articular cartilage showed a very short T2 [2].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Many types of treatments have been studied, both pharmacological and surgical, but one of the most difficult problems associated with research in this field is the lack of noninvasive methods to measure the condition of the articular cartilage during disease progression. Several studies on NMR imaging of the knee joint have been published (1)(2)(3)(4) including one which correlated NMR images of the rabbit knee joint with histologic evaluation (5). Although gross soft tissue changes in the joint can be discerned with NMR techniques, it has been difficult to measure noninvasively the biochemical status of cartilage in vivo in order to make serial examinations of the same joint.…”
Section: Introductionmentioning
confidence: 99%
“…MRI has been used to characterize a number of animal models of RA, such as adjuvant-induced RA in rats, [92][93][94][95] antigen-induced arthritis in rats 96,97 and rabbits, 98 interleukin-1 induced arthritis in rabbits, 99 and collagen type II induced arthritis in the rat. 100,101 In the last model the most distal joints (interphalangeal and metatarso-phalangeal joints) are affected prior to the proximal joints, 102 similar to the disease progression in man.…”
Section: Rheumatoid and Osteoarthritismentioning
confidence: 99%